Structural and optoelectronic properties of nickel doped CdO thin films deposited by spray pyrolytic technique (Nexo Revista Científica, 2023)
In this work, Cadmium oxide (CdO) and Nickle (Ni) doped cadmium oxide (CdO: Ni) thin films have been fabricated onto glass substrate by spray pyrolysis technique. The undoped and Ni-doped CdO thin films have been deposited at 400 °C heated glass substrate. The films' structure, morphology and optical properties were investigated & analyzed as a function of Ni doping level. As confirmed by different characterization, the preparade films have polycrystalline with cubic structure. Based on the results, the pure CdO films showed sharper and more intense diffraction patterns than Ni-doping films. Compared to the pure CdO films, the average grain size of the doped films decreases with increasing of doping level. Furthermore, the optical properties of Ni-doped CdO thin films showed lower absorption coefficient than pure films. However, the higher transparency of Ni-doped CdO films in the visible region consider a good window for the most optoelectronic devices applications. The energy band gap was tuned via Ni doping impurities and it increases as doping level increases.